Revealing the Power of Impact between Recruitment, Selection and Career Planning and Achieve Innovation then Entrepreneurship: A Study in U.A.E. - Naser, Mohamed (The Arab Journal of Administration, 2021)
This article investigates the power of impact between some human resource management (HRM) functions (or policies) and achieve innovation then entrepreneurship. It provides pragmatic evidence of the above- mentioned relationships through means of descriptive statistics and subsequently. It clarifies the effects over a regression analysis in the united arab emirates (UAE). The examination is made with statistical data collected from population of (10) pharmaceutical organizations which producing (manufacturing) drugs and medications out of (16) organizations were registered and licensed in this industry. Reference and data were used, carried out, and gathered between 2016 and 2019 respectively.